Temporal and spatial changes study of zooplankton abundance and biomass in the coastal water of the Latakia city - Durgham, Hani; Ikhtiyar, Samar; Mamish, Samer (Latakia University Journal -Biological Sciences Series, 2019)
This paper studied the total zooplankton abundance and biomass, and its relation with changes in some major ecological factors such as temperature and salinity. In two coastal areas located south and north of the Lattakia coast, each region has different environmental characteristics than the other. 30 marine samplings (15 each region) were carried out, at a rate of two samplings per season, during the study period between March 2017 and December 2018. Zooplankton Sampling were carried out horizontally draught at the surface layer, using a WP2-type plankton net with a diameter of 200 microns. The results showed that the total abundance of zooplankton changed significantly in the study areas during the different months of the year, with a clear tendency to increase the abundance in the southern area over the northern area of the Lattakia coast. This can be attributed to the effect of the nutrients carried by the Al-Shamali River, which play a clear role in enriching the seawater, thus increasing the abundance of zooplankton. The results showed that the abundance of fish eggs at sites far from shore is more likely than in near-shore locations, which can be attributed to environmental factors, shallow depth, degradation of fish habitats and pollution, which limit the production and abundance of fish eggs. The average of dry biomass of total zooplankton for both study areas was 4.85 mg dry weight /m3. تناولت الدراسة الغزارة الكلية للعوالق الحيوانية، وكتلتها الحيوية، وعلاقة ذلك مع تغيرات بعض العوامل البيئية الرئيسة مثل درجة الحرارة، والملوحة، وذلك في منطقتين ساحليتين جنوب وشمال مدينة اللاذقية. وتتصف كل منطقة بخصائص بيئية مختلفة عن المنطقة الأخرى. جرى القيام بثلاثين اعتيان (خمسة عشر اعتيان في كل منطقة)، بمعدل مرتين في كل فصل، وذلك خلال فترة الدراسة التي امتدت بين شهري آذار 2017 وكانون الأول 2018. جرى اعتيان العوالق الحيوانية من الطبقة السطحية، بالجر الأفقي باستعمال شبكة عوالق من نمط WP2، يبلغ قطر ثقوبها 200 ميكرون. بينت النتائج أن الغزارة الكلية للعوالق الحيوانية تغيرت تغيراً واضحاً في منطقتي الدراسة خلال أشهر السنة المختلفة، مع ميل واضح لزيادة الغزارة في المنطقة الجنوبية عن المنطقة الشمالية لساحل مدينة اللاذقية؛ والذي يمكن أن يعزى إلى تأثير المغذيات التي يحملها نهر الكبير الشمالي ويصبها في هذه المنطقة، والتي تلعب دوراً واضحاً في إثراء الوسط، وبالتالي في زيادة غزارة العوالق الحيوانية. كما بينت النتائج أن غزارة بيض الأسماك في المواقع البعيدة من الشاطئ أكثر منها في المواقع القريبة من الشاطئ، والذي يمكن أن يعزى إلى العوامل البيئية، وضحالة العمق، وتدهور المساكن الطبيعية للأسماك، والتلوث، التي تحد من انتاج بيض السمك وغزارته. تراوح متوسط الكتلة الحيوية الجافة للعوالق الحيوانية الكلية لكلا منطقتي الدراسة 4.85 مغ وزن جاف/م3.